SCREENING AND DETERMINATION OF EMULSIFICATION ACTIVITY OF SURFACTANT-PRODUCING BACTERIA FROM PALM OIL INDUSTRY LIQUID WASTE - Elsyana, Vida; Alvita, Livia Rhea; Afifah, Dian Ayu; Feladita, Niken; Setiawan, Panji (Universitas Tanjungpura, 2025)
Biosurfactants are natural surfactants produced by certain microorganisms (bacteria, fungi, and yeast) and are considered the best candidates for replacing synthetic surfactants. Bacteria isolated from oil spill areas have shown the ability to produce biosurfactants. This study enriched bacteria from anaerobic wastewater of palm oil industry in Lampung then isolated and screened natural surfactant-producing bacteria and measured their emulsification activity. Screening of surfactant-producing bacteria was carried out using oil spreading assay and their emulsification activity was measured based on the emulsification index (EI). The results of the study obtained 7 bacterial isolates and all showed positive results in the oil spreading assay. The highest emulsification index (EI) was produced by the fifth isolate (LAC5) with a value of 42.32%. These results show the potential for emulsification activity of biosurfactants produced by anaerobic wastewater bacteria from palm oil industry ponds.